(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Propolis is a mixture made by bees consisting of plant resins and metabolites, salivary enzymes and wax. Some species of bees add soil to this mixture forming geopropolis. This material is used in the defense of the hive as a physical barrier and antimicrobial agent, ensuring the health of the colony. Propolis has been extensively studied and several chemical constituents have been identified, mainly flavonoids, terpenes and phenolics. With the emerging microbial resistance to antibiotics, the interest in the search for active compounds, mainly secondary metabolites of plants, has been increasing significantly. In this paper, we describe the characteristics of the main species of native stingless bees found in South America, especially in Brazil, the ancestral use of propolis produced by them, its chemical composition and its potential for the development of new therapeutic compounds, along with the challenges that the survival of bees face.